Diseño de un puesto de trabajo para realizar la actividad de limpieza de piezas de bordado industrial, en la industria de manufactura textil. (2021)
Colombia has within its productive scope few large sectors, and within them, it has raw materials that facilitate some industries more than others. In this case, one of the most complete in the country is the textile industry. This sector has the capacity to handle 10.7% of the country's GDP, and generate jobs for 45% of the Colombian population.